Information-seeking and use of information resources among melanoma patients of German skin cancer centers Informationssuche und Nutzung von Informationsquellen durch Melanompatienten deutscher Hautkrebszentren - Brütting, Julia; Bergmann, Maike; Garzarolli, Marlene; Rauschenberg, Ricarda; Weber, Christiane; Berking, Carola; Tilgen, Wolfgang; Schadendorf, Dirk; Meier, Friedegund (Journal der Deutschen Dermatologischen Gesellschaft, 2018)
Background: This study aimed to explore the information-seeking behavior (ISB) of melanoma patients (MPs) and MP subgroups, in order to provide data for needs-based adaptation of information provision. Methods: In a cross-sectional survey in 27 German skin cancer centers, we explored characteristics of the ISB of MPs with the aid of a standardized questionnaire. Subgroup differences were determined with the chi-squared test and predictors of media preferences with logistic regression. Results: 67 % of the 529 participating MPs had clinical stage III or IV melanoma. Most of the participants (81 %) reported medical consultations as their regularly or frequently used information resource (IR). 58 % wished to have more advice about IRs from their physician. Only 8 % of MPs used the services of self-help groups and 12 % of MPs took advantage of the services of cancer counseling centers. The internet (63 %) and booklets (58 %) were reported to be the preferred media. Age, educational level, general need for information and lack of awareness of their own condition proved to be predictors for media preferences. Conclusions: Most MPs expected their physician to advise them about IRs they could use in addition to medical consultations. Peer support services were quite underused by MPs. The various preferences of media by MPs should be considered when developing and providing IRs.
CRIS-Team Scopus Importer:2023-03-23